Unsteady heat transfer measurements in a rotating gas turbine stage - Hilditch, M; Hilditch, Mary Anne (1989)
﻿ As the performance required of high pressure turbines continues to increase, there is a need to investigate many details of the flow which occur in a gas turbine stage that were previously overlooked. These include the effects of rotation and three-dimensional flow as well as unsteady effects due to the relative motion of the blade rows. In order to obtain a better understanding of the turbine flowfield a new transient facility has been commissioned in which aerodynamic and heat transfer measurements can be undertaken in a full stage turbine at engine representative conditions. The previously used technique of measuring the heat transfer rate by mounting thin film gauges on models manufactured from machineable glass ceramic was not suitable for use on the rotor blade because of the high stress levels involved. An alternative technique has been developed in which a metal turbine blade is coated with an insulating layer of enamel and thin film gauges painted on top. The developments in signal processing and calibrations which were necessary for the use of this type of thin film gauge are discussed in detail. Signal conditioning electronics have been developed which permit amplification of the thin film gauge output to a higher level within the rotating frame before transmission through a slipring. Extensive tests have been undertaken, in a purpose built spinning rig, to establish the effects of rotation on the performance and mechanical integrity of the instrumentation and associated electronics. The heat transfer measurements recorded in the rotor facility to date are presented and compared with data from a previous two-dimensional simulation of wake passing flow on the mid-height section of the same blade.